Genetic basis of anthracyclines cardiotoxicity: Literature review - M. Yu. Sinitsky (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
The purpose of this review was to systematize data on molecular genetic markers of increased risk of cardiotoxic effects, as well as to search for risk and protective variants of candidate genes. Today, the therapy of malignant neoplasms is based on the use of anthracyclines – drugs of the cytostatic mechanism of action. Along with their effectiveness, these drugs can have a cardiotoxic effect on cardiomyocytes by increasing the amount of reactive oxygen species and disrupting mitochondrial biogenesis. Pathological disorders lead to an increased risk of myocardial dysfunction and a number of other cardiovascular pathologies in patients receiving chemotherapy using anthracyclines. The cardiotoxic effect of anthracyclines leads to cardiomyopathy, heart failure, myocardial infarction, and thrombosis. Early detection of cardiotoxic damage leads to reducing the negative effects of these drugs due to changes in chemotherapy tactics. It is known that the risk of cardiotoxic myocardial damage is genetically determined and controlled by more than 80 genes. In this review, the description of basic molecules such as ATP-binding cassette transporters and solute carrier family (SLC transporters), carbonyl reductase, molecules of antioxidant defense, xenobiotic and iron metabolism was performed. In addition, a special attention is paid to the study of epigenetic and post-translational regulation. The available data are characterized by some inconsistency that may be explained by the ethnic differences of the studied populations. Thus, a more detailed research of various ethnic groups, gene-gene interactions between potential candidate genes and epigenetic regulation is necessary. Thus, understanding the contribution of genetic polymorphism to the development of cardiotoxicity will help to assess the individual risks of cardiovascular pathology in patients with various types of cancer, as well as reduce the risk of myocardial damage by developing individual preventive measures and correcting chemotherapy.